Biopolymeric electrolyte based on glycerolized methyl cellulose with NH4Br as proton source and potential application in EDLC - Kadir, M.F.Z. (Institute for Ionics, 2018)
In the present work, biopolymer electrolyte films based on MC doped with NH4Br salt and plasticized with glycerol were prepared by solution casting method. Fourier transform infrared (FTIR) spectroscopy analysis confirms the interaction between MC, NH4Br, and glycerol. X-ray diffraction (XRD) explains that the enhancement of conductivity is affected by the degree of crystallinity. This result is verified by field emission scanning electron microscopy (FESEM). For unplasticized system, sample containing 25Â wt of NH4Br possesses the highest ionic conductivity of (1.89Â Â±Â 0.05)Â ÃÂ 10â4Â SÂ cmâ1. The addition of 30Â wt glycerol increases the conductivity value up to (1.67Â Â±Â 0.04)Â ÃÂ 10â3Â SÂ cmâ1. The conduction mechanism was best presented by the correlated barrier hopping (CBH) model. The linear sweep voltammetry (LSV) and cyclic voltammetry (CV) result confirms the suitability of the highest conducting electrolyte to be employed in the fabrication of electrochemical double layer capacitor (EDLC). Â© 2017, Springer-Verlag GmbH Germany.